1998
DOI: 10.1073/pnas.95.9.4831
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the catalytic domain of avian sarcoma virus integrase with a bound HIV-1 integrase-targeted inhibitor

Abstract: The Retroviral integrase (IN)ʈ catalyzes the integration of reversetranscribed viral DNA into the host genome in two steps called processing and joining (1-3). These reactions are chemically similar, proceeding via nucleophilic attack on the DNA by a donor hydroxyl group (water or ribose 3Ј OH), activated by the catalytic site of the enzyme. In vitro, these reactions require only divalent cations and water as cofactors. The in vitro reactions are fastest with Mn 2ϩ as the metal cofactor, although Mg 2ϩ also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 35 publications
4
90
1
Order By: Relevance
“…These residues were therefore proposed to directly bind the required metal cofactors. Later studies showed that divalent cations, such as Ca Binding studies of human immunodeficiency virus type 1 IN and ASV IN with an inhibitor targeted against human immunodeficiency virus type 1 IN showed comparable inhibition effects, but the crystal structure of an inhibitor-catalytic core domain complex was determined only for ASV IN (8). One interesting observation during that study was the rotation of the side chain of the central acidic residue, Asp-64, around the C␣OC␤ bond.…”
Section: Integrase (In)mentioning
confidence: 97%
“…These residues were therefore proposed to directly bind the required metal cofactors. Later studies showed that divalent cations, such as Ca Binding studies of human immunodeficiency virus type 1 IN and ASV IN with an inhibitor targeted against human immunodeficiency virus type 1 IN showed comparable inhibition effects, but the crystal structure of an inhibitor-catalytic core domain complex was determined only for ASV IN (8). One interesting observation during that study was the rotation of the side chain of the central acidic residue, Asp-64, around the C␣OC␤ bond.…”
Section: Integrase (In)mentioning
confidence: 97%
“…In our previous reports (21,22), we noted a new conformation of the active-site loop, as well as vastly different conformations of the side chain of Asp64; therefore, in the present study, we sought to minimize model bias. The refinement was cross-validated by the R free index (24), which was calculated using 10% of all reflections.…”
Section: Methodsmentioning
confidence: 99%
“…Only two conserved water molecules interact with the protein via a single hydrogen bond. About one-fourth of these conserved water molecules (21) are located within the crystallographic dimer interface, and four of them (Wat402, Wat413, Wat470, and Wat472) clearly play a direct role in stabilizing dimerization.…”
Section: Structures Of Asvin-trn and D64n-trnmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of key amino acid residues involved in the binding of potential drugs, and therefore which residues are likely to mutate under therapeutic pressure, would inevitably help researchers stay one step ahead of drug-resistant viral strains. A co-crystal structure of one of our inhibitors was previously solved with the ASV-IN (4,5). This complex was subsequently used as a surrogate structure to discover IN inhibitors through highthroughput docking studies (6).…”
mentioning
confidence: 99%